2022
DOI: 10.3389/fnut.2022.886224
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maternal caffeine and coffee intake and pregnancy loss: A grading of recommendations assessment, development, and evaluation-assessed, dose-response meta-analysis of observational studies

Abstract: BackgroundNumerous studies report an association between coffee or caffeine consumption and pregnancy loss; however, the nature and strength of this relationship have not been clearly established. Based on recent studies, our meta-analysis aimed to test whether a dose–response relationship between coffee or caffeine consumption and pregnancy loss exists.MethodsWe searched for articles in PubMed, Web of Science, and Scopus published until May 2022. Two independent reviewers extracted data and rated the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
5
0
2
Order By: Relevance
“…Therefore, patients should limit their caffeine intake to less than 300 mg/d and consider further limitation to less than 99 mg/d. 117,[119][120][121][122][123]…”
Section: Caffeine Tobacco and Alcoholmentioning
confidence: 99%
“…Therefore, patients should limit their caffeine intake to less than 300 mg/d and consider further limitation to less than 99 mg/d. 117,[119][120][121][122][123]…”
Section: Caffeine Tobacco and Alcoholmentioning
confidence: 99%
“…Estes benefícios têm de ser ponderados em função de alguns potenciais riscos associados ao consumo de café, como ansiedade, insônia, cefaleias, tremor e palpitações, sintomas que surgem mais frequentemente como consequência de um consumo de doses mais elevadas de café (O' Keefe et al, 2018;Poole et al, 2017) e muitas vezes resultantes de outros fatores associados ao consumo de café (consumo de tabaco, álcool). Também, mulheres gestantes deverão ter em conta o possível impacto do café no desenvolvimento fetal (Jafari et al, 2022;Williford et al, 2023), nos partos prematuros (L. W. Chen et al, 2016;Greenwood et al, 2014;Z. X. Li et al, 2016;Rhee et al, 2015) e aborto espontâneo (Jafari et al, 2022;Lyngsø et al, 2017) , assim como as questões em aberto sobre o impacto do consumo de café na osteoporose e fraturas associadas (Hallstrom et al, 2013;Johansson et al, 1992;Kiel et al, 1990).…”
Section: Caféo Nutracêutico Mais Efetivo?unclassified
“…Também, mulheres gestantes deverão ter em conta o possível impacto do café no desenvolvimento fetal (Jafari et al, 2022;Williford et al, 2023), nos partos prematuros (L. W. Chen et al, 2016;Greenwood et al, 2014;Z. X. Li et al, 2016;Rhee et al, 2015) e aborto espontâneo (Jafari et al, 2022;Lyngsø et al, 2017) , assim como as questões em aberto sobre o impacto do consumo de café na osteoporose e fraturas associadas (Hallstrom et al, 2013;Johansson et al, 1992;Kiel et al, 1990).…”
Section: Caféo Nutracêutico Mais Efetivo?unclassified
“…The adverse environment during pregnancy can be divided into exogenous factors and maternal factors. It has been found that most of the adverse environmental factors can cross the placental barrier and directly affect embryonic or fetal development, such as polycyclic aromatic hydrocarbons, [4] particulate matter 2.5 (PM2.5), [5,6] dexamethasone, [7,8] heavy metals, [9,10] nicotine, [11,12] ethanol, [13] caffeine, [14,15] cocaine, [16,17] and opioids, [17][18][19] etc. Besides, some environmental factors that cannot cross the placental barrier can indirectly affect fetal development by disrupting the structure and function of the placenta, such as exposure to cobalt and chromium nanoparticles causing placental autophagic flow impairment and interleukin (IL)-6 release, which disrupts fetal astrocytes and neurons development.…”
Section: The Adverse Environment During Pregnancy Leads To the Occurr...mentioning
confidence: 99%